(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The article describes measures taken by banks to attract funds from legal and natural persons, restrictions and privileges in providing deposits to the population, as well as the control of the activities of commercial banks in attracting deposits by the Central Bank, researches about laws and regulations will be covered.